Important advances in regenerative medicine. A vision to the future of ophthalmology: Avances importantes en medicina regenerativa. Una visión al futuro de la oftalmología - Hernández, Rafael Iván (2023)
The treatment of corneal lesions continues to be a topic of great interest. However, despite the development of new technologies and due to the slow evolution and uncertain healing of corneal lesions, they still represent a public health problem since patients can be affected for life, affecting the family and the health system due to the costly and uncertain response to treatment. For this reason, the need arises to seek therapeutic alternatives to treat these patients.